Analisis Maslahat terhadap Pertimbangan Hakim dalam Memutus Perkara Sengketa Harta Waris yang dihibahkan: Studi Putusan Banding Nomor 0020/Pdt.G/2019/PTA.Bdl - Syarifah, Inayatul (Fakultas Syariah INSURI Ponorogo, 2021)
The purpose of this study is to determine the basis for consideration of religious court judges and religious high judges in granting or rejecting applications for inheritance cases that have been granted. This type of research is library research (library research), descriptive research using qualitative methods. Whereas the power of attorney to compare M. Fadlil Hadi's power of attorney to Dr. M. Yaman, S.H., M.H. and Ramid, S.H. The date February 9 2018 is invalid. The limitation of presenting a grant as an illustration of a case regarding a lawsuit for inherited land disputes that has been granted in terms of the Maslahah Mursalahah, is to respect and fulfill a sense of justice for other war experts, even though the jurists do not. KHI is based on consideration of benefit (providing benefits) and avoiding harm.